Method of performance of the drawing “Plaster ornament” (Pedagogy of Higher and Secondary Education, 2006)
Methodical advices which will help studying regional pedagogical lyceum for rural young people correctly to organize the prosecution of task the picture «Gipseous decorative pattern are expounded in the article».
Keywords: gtpscous decorative pattern; proportions; rhythm; personal touches